The power of critical thinking effective reasoning about ordinary and extraordinary claims. - Vaughn, Lewis (Oxford University Press, 2010)
Part I: Basics. The power of critical thinking -- Obstacles to critical thinking -- Making sense of arguments -- Part II: Reasons. Reasons for belief and doubt -- Faulty reasoning -- Part III: Arguments. Deductive reasoning : propositional logic -- Deductive reasoning : categorical logic -- Inductive reasoning -- Part IV: Explanations. Inference to the best explanation -- Judging scientific theories -- Judging moral arguments and theories